Smart Containment : Lessons from Countries with Past Experience - Fotiou, Alexandra; Lagerborg, Andresa (Washington, D.C. : International Monetary Fund, 2021)
Following the Great Lockdown in 2020, it is important to take stock of lessons learned. How effective have different containment measures been in slowing the spread of Covid-19? Have containment measures been costly in terms of economic growth, fiscal balances, and accumulated debt? This paper finds that countries with previous SARS experience acted fast and "smart", and were able to contain the virus by relying mainly on public health measures - testing, contact tracing, and public information campaigns - rather than stay-at-home requirements. Using past coronavirus outbreaks as an instrumental variable, we show that countries with past experience were able to contain the virus in a smart way, reducing transmission and deaths while also experiencing higher economic growth in 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Health Behavior; Informal Economy; Underground Econom